Pengembangan Model Pembelajaran Renang Melalui Materi Pengenalan Aktivitas Air Di Sekolah Dasar : (The Development of a Swimming Learning Model Through The Introduction of Water Activities in Primary School) - Herdianto, Herdianto; Iyakrus, Iyakrus; Usra, Meirizal (Jurnal Ilmu Olahraga dan Kepelatihan Indonesia, 2020)
This study aims to develop a swimming learning model through the introduction of water activities in elementary schools. The learning model is in accordance with the psychomotor characteristics of students and helps students in learning the introduction of water activities. The method used in this research is the method of development. The subjects in this study were 56 students of grade II SD Banding Agung. This development research uses the ADDIE development model consisting of the stages of Analysis, Design, Development, Implementation and Evaluation. Data collection techniques in this study include validation sheets, questionnaires, and tests of basic water activity abilities. Expert testing is carried out by material experts and psychomotor experts. The results of the validation of the resulting learning model meet the validation requirements according to the student's psychomotor stages and learning objectives. The one to one test stage obtained the results of the questionnaire all the sample students agreed that mode. In the small group test, the average gainscore result was 0.75 and was included in the high category and the results of the student motivation questionnaire were 92.5%. At the implementation stage of the learning model, the learning results obtained from a gainscore of 0.78 are in the high category and 82.975% agree that the model used is fun and provides motivation to dare to play in the water. The implication of this research is that the development of a swimming learning model through the introduction of water activities is valid, effective and practical and can be used by physical education teachers in elementary schools. Abstrak. Penelitian ini bertujuan untuk mengembangkan model pembelajaran renang melalui materi pengenalan aktivitas air di sekolah dasar. Model pembelajaran tersebut sesuai dengan karakteristik psikomotorik siswa serta membantu siswa dalam pembelajaran pengenalan aktivitas air. Metode yang digunakan dalam penelitian ini adalah metode pengembangan. Subjek dalam penelitian ini adalah siswa kelas II SD banding Agung sebanyakÂ  56 orang siswa. Penelitian pengembangan ini menggunakan model pengembanganÂ  ADDIE terdiri atas tahapan Analysis, Design, Development, Implementation dan Evaluation Teknik pengumpulan data dalam penelitian ini yaitu meliputi lembar validasi, angket, dan tes kemampuan dasar aktivitas air. Uji ahli dilakukan oleh ahli materi dan ahli psikomotorik. Hasil validasi model pembelajaran yang dihasilkan memenuhi syarat validasi sesuai dengan tahapan psikomotorik siswa dan tujuan pembelajaran. Tahap uji one to one didapatkan hasil angket semua siswa sample setuju bahwa mode. Pada tes small group didapatkan rata-rata hasil gainscore 0,75 dan masuk dalam kategori tinggi dan hasil angket motivasi siswa didapatkan 92,5%. Pada tahap implementasi model pembelajaran didapatkan hasil gainscore 0,78 termasuk kategori tinggi dan 82,975% setuju kalau model yang digunakan menyenangkan dan memberikan motivasi untuk berani bermain di air. Implikasi dari penelitian ini bahwa pengembangan model pembelajaran renang melalui materi pengenalan aktivitas air ini valid, efektif dan praktis serta dapat digunakan bagi guru penjas di sekolah dasar .